Corporate Governance in Cooperatives: a look at publications, trends, and relevance - Becerra Arévalo, Jairo Alfonso; Giraldo Pérez, Yudy Elena (REVESCO. Revista de Estudios Cooperativos, 2025)
This article presents the results of a bibliometric and documentary analysis, its evolution and trends, on corporate governance in the solidarity sector, with an emphasis on cooperatives, during the period 1995-2024. The research is based on the analysis of documents indexed in the Web of Science (WoS) and Scopus databases, constructing indicators of productivity, impact and structure using data analysis tools such as Excel, VOSviewer and the Bibliometrix package in R. The results show a growing academic interest in the study of corporate governance in solidarity sector organisations, with an increase in academic productivity, a wide dispersion and dissemination among authors and journals, as well as a diversity of analytical-oriented approaches, where the role of boards of directors in the processes of cooperative organisations and the use of mainly quantitative approaches for their analysis, and the application of mathematical-statistical models in measuring corporate governance decisions in cooperatives are relevant. The study concludes that, despite advances in the scientific study of corporate governance in cooperatives, it remains a developing field of study, with theoretical and methodological gaps, which represents an opportunity for future research.